G-stability one-leg hybrid methods for solving DAEs - P. Agarwal; Iman H. Ibrahim; Fatma M. Yousry (Advances in Difference Equations, 2019)
Abstract This paper introduces the solution of differential algebraic equations using two hybrid classes and their twin one-leg with improved stability properties. Physical systems of interest in control theory are sometimes described by systems of differential algebraic equations (DAEs) and ordinary differential equations (ODEs) which are zero index DAEs. The study of the first hybrid class includes the order of convergence, A(α)-stability, stability regions, and G-stability for its one-leg twin in two cases: for step ( k=1 $k=1$) and steps ( k=2 $k=2$). For the second class, G-stability of its one-leg twin is studied in two cases: for steps ( k=2 $k=2$) and steps ( k=3 $k=3$). Test problems are introduced with different step size at different end points.